Komodifikasi Audiens-Penonton dalam Program Ajang Pencarian Bakat The Voice: All-Stars GTV - Gilar Dido Bagaskoro (Communication and Islamic Broadcasting Study Program, Faculty of Da'wah and Communication, State Islamic University Sunan Kalijaga Yogyakarta, 2022)
This research examines the audience commodification process in the search program The Voice: All-Stars GTV. This study uses a qualitative-descriptive method with the political economy theory approach of Vincent Mosco's media. The results of the study show that audience commodification occurs in The Voice: All-Stars GTV in several stages. First, when the event succeeds in attracting advertisers to become the main sponsor. Second, when involving the audience when voting to support the contestants through the RCTI+ and MotionPay applications with top-up balances. The two applications were developed by MNC Group as the owner of the media that broadcast The Voice: All-Stars GTV. Apart from being successful in gaining advertisements, the television stations also succeeded in promoting other products in the form of applications developed by the company.